Kajian Kriminologi Terhadap Anak (Pelaku) Tindak Pidana Pencurian Sepeda Motor Dengan Kekerasan - Rahmayanti Rahmayanti (Pusat Riset dan Inovasi Nasional, 2023)
Violent motorbike theft crimes committed by minors are increasing in the 2020-2023 period. The criminological approach is an important and strategic entity in finding the root causes of violent motorbike theft crimes committed by children so that it can provide appropriate countermeasures. appropriate. The formulation of the problem in this research consists of the criminological perspective on children as perpetrators of the crime of motorbike theft with violence, and the factors that result in children becoming perpetrators of the crime of motorbike theft with violence. The crime of motorbike theft with violence committed by children in the 2020-2022 period was 44 cases, 38 of which were successfully resolved. Factors that influence children in committing crimes of motorbike theft with violence include economic factors, environmental factors, drug factors, parental approach and supervision factors, hedonic factors, crime scene factors, presence of guardians, and religious factors. Efforts to deal with this crime are divided into 2 types, namely preventive efforts and repressive efforts.